Fabric Defect Detection Using Local Homogeneity Analysis and Neural Network. (17th March 2015) - Rebhi, Ali; Benmhammed, Issam; Abid, Sabeur; Fnaiech, Farhat
Abstract : In the textile manufacturing industry, fabric defect detection becomes a necessary and essential step in quality control. The investment in this field is more than economical when reduction in labor cost and associated benefits are considered. Moreover, the development of a wholly automated inspection system requires efficient and robust algorithms. To overcome this problem, in this paper, we present a new fabric defect detection scheme which uses the local homogeneity and neural network. Its first step consists in computing a new homogeneity image denoted asH -image. The second step is devoted to the application of the discrete cosine transform (DCT) to theH -image and the extraction of different representative energy features of each DCT block. These energy features are used by the back-propagation neural network to judge the existence of fabric defect. Simulations on different fabric images and different defect aspects show that the proposed method achieves an average accuracy of 97.35%.